Diversity and similarity of melon (Cucumis melo L.) groups and determination of distinguishing morphological characters - HELFI EKA SAPUTRA; MUHAMAD SYUKUR; WILLY BAYUARDI SUWARNO; SOBIR SOBIR (Society for Indonesian Biodiversity, 2022)
Abstract. Saputra HE, Syukur M, Suwarno WB, Sobir. 2022. Diversity and similarity of melon (Cucumis melo L.) groups and determination of distinguishing morphological characters. Biodiversitas 23: 6254-6261. Characterization is an important activity for the study of genotype diversity and similarity. The study was aiming at obtaining information about the diversity and similarity of melon groups and to determine morphological characters as differentiators between melon groups. The genotypes tested were IPB240, IPB283, IPBM21, IPBM23, IPBME5, IPBMETA9, UME20, UME38, UME39, UME90, UME91, UME98, UME99, UME100, UME101. Characterization was based on UPOV and IPGRI guidelines for qualitative and quantitative characters. Two qualitative characters showed no variation in all tested genotypes, namely sex expression (EK) and secondary skin color outside the groove (WKSDA). Qualitative characters that have high diversity were groove color (WA), maximum width between grooves (LMAA), groove color intensity (IWA), and flower stalk thickness (KTBN). The UME98 genotype had the most different color appearance from the other genotypes on the heatmap. The color and depth of fruit grooves are distinguishing characteristics of all genotypes. There were genotype differences in the inodorus and reticulatus types. Unlike the IPBMETA9 genotype, UME100, UME101, and UME38 formed the same clusters with the characteristics of the makuwa group. Melon group makuwa had different characteristics with the inodorus and reticulatus groups. The distinguishing characters for the makuwa type were groove depth, ratio length to diameter, the diameter of hermaphrodite flower stalks, fruit diameter, and fruit skin thickness. Melon groups in the inodorus and reticulatus groups had high similarities, making it difficult to find specific characters in all melon genotypes observed.